Bioanalytical qualification of clinical biomarker assays in plasma using a novel multi-analyte Simple Plex™ platform. (December 2016) - Gupta, Vinita; Davancaze, Teresa; Good, Jeremy; Kalia, Navdeep; Anderson, Michael; Wallin, Jeffrey J; Brady, Ann; Song, An; Xu, Wenfeng
Aim: Immune-checkpoint inhibitors are presumed to break down the tolerogenic state of immune cells by activating T-lymphocytes that release cytokines and enhance effector cell function for elimination of tumors. Measurement of cytokines is being pursued for better understanding of the mechanism of action of immune-checkpoint inhibitors, as well as to identify potential predictive biomarkers.Results: In this study, we show bioanalytical qualification of cytokine assays in plasma on a novel multi-analyte immunoassay platform, Simple Plex ™ . The qualified assays exhibited excellent sensitivity as evidenced by measurement of all samples within the quantifiable range. The accuracy and precision were 80–120% and 10%, respectively.Conclusion: The qualified assays will be useful in assessing mechanism of action cancer immunotherapies.